Peran Unit Pelayanan Perempuan Dan Anak (PPA) Satreskrim Polresta Banyumas Dalam Menanggulangi Tindak Pidana Persetubuhan Terhadap Anak Dibawah Umur - Tri Rahayu; Arif Awaludin; Ikama Dewi Setia Triana; Arka Atyanta (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2024)
This paper aims to analyze the role of the Women and Child Services Unit (PPA) of Satreskrim Polresta Banyumas in dealing with the crime of prostitution against minors and the factors causing the crime in the territory of the law of Polrest Banyumas. A qualitative approach is used to collect data through interviews, observations, and document analysis. The results of the research show that the PPA Unit has a significant role in dealing with cases of sexual abuse against minors, including in the prevention, law enforcement, and victim recovery aspects. The causes of such crimes include low awareness of children's rights, gender inequality, lack of adequate sexual education, and vulnerable socio-economic conditions. The conclusions reaffirmed the need for collaborative efforts between various parties, including government agencies, communities, and non-governmental organizations, in improving child protection and combating sexual offences against minors in the area of law of Polresta Banyumas. This research contributes to a greater understanding of the dynamics of dealing with crimes of sexual immorality against minors and the efforts that can be made to address them in a holistic way. Keywords: Women's and Children's Service Unit, underage children